Recirculation loop in CFF/TFF single use flow path - LIDERFELT KARL AXEL JAKOB; NUTALAPATI SASI KUMAR; VERNEKAR AJIT S; KARMARKAR NACHIKET; SHARMA AMIT K; GEBAUER KLAUS; LUNDSTROM FREDRIK OSKAR (2025)
The disclosed subject matter relates to an automated CFF/TFF system that provides operations of system treatment of solutions (e.g., buffers) with the system and filtration of solutions (e.g., biological fluids) that can be done continuously without having to reconstruct the system (e.g., rewiring fluid conduits), which may compromise the integrity of the system. Thus, the risk of contamination will be reduced, the amount of buffer required will be reduced, and time will be saved for the filtration process. 公开的主题涉及一种自动化CFF/TFF系统，其提供利用系统处理溶液(如缓冲液)的系统处理和溶液(例如生物流体)的过滤的操作，该操作可连续地完成，而不必重新构造系统(如对流体导管重新布线)，这可损害系统的完整性。因此，将降低污染风险，减少所需缓冲液的量，并且将为过滤过程节省时间。